Tris(3-methoxypropyl)tin aminobenzoates as potentially trypanocidal agent - Semenyšínová, Lenka; Handlíř, Karel (Univerzita Pardubice, 2004)
A set of tris(3-methoxypropyl)tin aminobenzoates and N-(4,6-diamino-1,3,5-triazin-2-yl-)aminobenzoates as compounds with potential trypanocidal activity have been prepared and their solubility in water was determined. On the basis of their 13C and 119Sn NMR spectra and IR spectra, bonding relations in these esters are discussed and a model of the trigonal-bipyramidal coordination polyhedra around central tin atom is proposed.